Pengaruh Media Sosial Instagram @LocalPrideIndonesia Terhadap Minat Beli Followers - Novaldy Rhojabill Suwasano; Mochammad Djauhari (DIGICOM : Jurnal Komunikasi dan Media, 2022)
The development of technology and communication is currently experiencing a fairly rapid development, as is Instagram social media. Currently, social media is developing very rapidly following the times, one of which is Instagram can be used as a medium for doing business. Instagram is very easy to attract the interest of the audience or followers with a few posts from these accounts. Currently the apparel business is very much in demand by many people, especially regarding local brands. So in this study, entitled The Effect of the @localprideindonesia Instagram Account on Followers Buying Interest, aims to determine the level of influence of the @localprideindonesia Instagram account on followers' buying interest. In this study, researchers used the S.O.R Theory (Stimulus, Organism, Response). The theory that relates message communication and reaction. In this study using quantitative research methods by collecting data using questionnaires and the sampling technique used in this study using simple random sampling with the number of respondents as many as 100 people. Based on the research that has been done, the researchers get the results that there is a significant effect of the Instagram @localprideindonesia variable on buying interest